Интертекстуальный дискурс в романе Л. Улицкой „Медея и её дети” - Коршунова, С. (Питання літературознавства, 2009)
Досліджується інтертекстуальний діалог між відомим античним міфом і авторською його інтерпретацією в умовах нової парадигми мислення та цінностей, породжених, зокрема, і тою мультикультурною ситуацією, в якій створювався роман Людмили Уліцкої „Медея та її діти”. The article deals with the intertextual dialogue between the famous ancient myth and its author’s interpretation under the circumstances of the changed paradigm of thinking and values which was caused, in particular, by that multicultural situation in which the novel ‘Medea and Her Children’ by L.Ulitskaya was being created.